The afro-cesar agrofood system reconfiguration: from coal mining to sustainability transition - Fernández, Ana María Moreno; Velandia, Diego Alejandro Salinas; Osorio, Álvaro Acevedo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2025)
This study analyses food security impacts of the agri-food system in the Afro-descendant Community Council of La Jagua de Ibirico (Cesar – Colombia), structured for many years on the economic dependence on coal mining. Using a qualitative-descriptive approach, semi-structured interviews were conducted with farming families and focus groups with key members of the community. The research identifies the environmental, social and economic drivers that influence production and food security. The results show that coal mining activity in this community has reduced local food production, increased dependence on external sources and increased the risks of food insecurity. The lack of infrastructure and limited access to resources for agricultural activities aggravate this condition of food vulnerability. However, the study also highlights opportunities for recovery, such as the adoption of agroecological practices that promote food sovereignty and strengthen community resilience. The findings underline the need for policies that support sustainable agricultural production and reduce dependence on external markets.